Prevalence of Multi Drug Resistant (MDR) in Gram Negative Bacterial isolates from different clinical samples - Kumar Verma, Mahendra; Shrimali, Arushi; Choudhary, Ajay Kumar; Yadav, Kuldeep (Journal of Neonatal Surgery, 2025)
Antibiotic resistance is a worldwide problem that can cross international boundaries and spread between continents very easily and speedily. World health readers have described antibiotic resistant organisms as “nightmare bacteria” that pose a “catastrophic threat” to people in every country in the world. The use of antibiotic is the single most important factor leading to antibiotic resistance around the world. Emergence of resistance to multiple antimicrobial agents in pathogenic bacteria has become a significant public health threat as there are fewer, or even sometimes no, effective antimicrobial agents available for infections caused by these bacteria. Gram-positive and Gram-negative bacteria are both affected by the emergence and rise of antimicrobial resistance. As this problem continues to grow, harmonized definitions with which to describe and classify bacteria that are resistant to multiple antimicrobial agents are needed, so that epidemiological surveillance data can be reliably collected and compared across healthcare settings and countries. Present study will help to know the prevalent drug resistant bacterial strain and their resistance pattern and also to detect the incidence of Multi drug resistant (MDR) in Gram negative bacterial isolates in tertiary care hospital. This Prospective study will be conducted in central laboratory, Department of Microbiology, Pacific Institute of Medical Sciences Udaipur. Total 371 gram negative bacterial isolates were obtained in two and half year study. Male patients 53% and female patient's 47%. most of the bacteria isolated from Urine specimen 157 followed by pus sample 73. MDR was reported in GNB about 61.18%, Klebsiella spp 120 was the most reported bacteria in our study followed by E. coli, 112.